1977
DOI: 10.1002/dev.420100308
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in the maternal behavior of rats rearing malnourished offspring

Abstract: Investigations of maternal behavior of mothers fed a low-protein diet indicated deficits in retrieval and in the rate of nest-building. In addition, they indicated a concomitant increase in time spent with young when assessed during periods not associated with the retrieval/nest-building test session. The adrenalectomized mother, another case that produces growth-stunted progeny, was compared with both low-protein and control mothers for maternal behavior. Unlike the low-protein mother, the adrenalectomized mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 16 publications
(3 reference statements)
3
29
1
Order By: Relevance
“…One possible explanation for the decreased somatic growth observed in the dexamethasone-treated pups is inadequate nutritional intake during the postnatal period due to inability to attach to the mother's nipples or poor suckling. Although we did not quantify these behaviors, it has been shown that the dam spends more time providing nutrition, stimulation, and warmth to a litter that is perceived to have poor health (15,65,91,101). On the other hand, dexamethasone prevents adequate growth, rapidly inducing protein catabolism beyond the capacity for an anabolic state, resulting in reduced growth and lean body mass (10,62,90,99).…”
Section: Somatic and Brain Growthmentioning
confidence: 99%
“…One possible explanation for the decreased somatic growth observed in the dexamethasone-treated pups is inadequate nutritional intake during the postnatal period due to inability to attach to the mother's nipples or poor suckling. Although we did not quantify these behaviors, it has been shown that the dam spends more time providing nutrition, stimulation, and warmth to a litter that is perceived to have poor health (15,65,91,101). On the other hand, dexamethasone prevents adequate growth, rapidly inducing protein catabolism beyond the capacity for an anabolic state, resulting in reduced growth and lean body mass (10,62,90,99).…”
Section: Somatic and Brain Growthmentioning
confidence: 99%
“…In a more detailed second study, Wiener et al (12) reported that dams maintained on a low protein diet retrieved less than wellnourished dams after some retrieval tests, but during periods not associated with the tests, malnourished dams spent more time with their pups. Several other literature reports demonstrated that malnourished dams spend more time with litters when observations are made in the home cage with little disturbance of dam behavior (4,12,13,17,20).…”
Section: Introductionmentioning
confidence: 97%
“…The methods used to produce undernutrition in rats are accompanied by changes in mother-pup interaction (8)(9)(10)(11)(12) and it has been proposed that changes in maternal behavior tend to minimize the effects of undernutrition on offspring growth and development (13,14). Other studies have indicated that the changes in maternal behavior cause either beneficial effects (15) or no effect on the later behavior of offspring (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations